Technology, power, and creativity in China’s Wanghong industry: A creator-centric analysis of digital cultural production - Guo, Qinghao; Rungsrisawat, Somdech (Edelweiss Applied Science and Technology, 2025)
This study examines how technology integration shapes power dynamics and creative labor management in China’s wanghong (internet celebrity) industry, focusing on the moderating roles of collaboration and job satisfaction. Using a mixed-methods approach, we analyzed survey data from 600 university students and conducted semi-structured interviews with 20 stakeholders, including creators, experts, and audiences. Quantitative results from structural equation modeling revealed that technology integration significantly enhances both power dynamics and creative labor management. However, collaboration and job satisfaction negatively moderated these relationships, suggesting that social and psychological factors may offset technological benefits. Qualitative findings uncovered a dualistic power dynamic where digital tools empower creators, but platform algorithms impose structural constraints. Additionally, collaboration was found to both expand opportunities and dilute creative autonomy, while job satisfaction reduced reliance on technological systems. The study concludes that technology’s role in digital cultural production is contingent on socio-technical interactions, challenging deterministic narratives of platform empowerment. These findings have implications for platform governance, suggesting the need for balanced policies that safeguard creator autonomy while optimizing technological affordances.